Rmauthairili - (:unkn) unknown (Chinu Rani Barman,Borbhuiya Lane, Rongpur Pt. IV, Silchar-, 2016)
This is the collection of poems of Biswajyoti barman. In this book dimasa language literature is described.
Keywords: Dimasa; Rmauthairili; Literature; Dimasa; Dimasa